Disruption of G0/G1 switch gene 2 (G0S2) reduced abdominal fat deposition and altered fatty acid composition in chicken. Issue 1 (7th August 2018) - Park, Tae Sub; Park, Joonghoon; Lee, Jeong Hyo; Park, Jeong-Woong; Park, Byung-Chul
ABSTRACT: Chicken as a food source is one of the most widespread domestic animals, and it has been used extensively as a research model. The clustered regularly interspaced short palindromic repeats (CRISPR)‐CRISPR‐associated protein 9 (Cas9) system is the most efficient and reliable tool for precise genome‐targeted modification and has generated considerable excitement for industrial applications, as well as biologic science. Unlike in mammals, germline‐transmittable primordial germ cells (PGCs) in chicken were used as an alternative strategy for the production of genetically altered chickens. Here, by combining the CRISPR‐Cas9 platform and germ cell‐mediated germline transmission, we generated G0 /G1 switch gene 2 ( G0S2 )knockout (KO)chickens, and G0S2 null KO chickens showed a dramatic reduction of abdominal fat deposition without affecting other economic traits. Additionally, G0S2 null KO chickens had altered fatty acid compositions in their blood and abdominal fat compared with wild‐type chickens under normal dietary conditions. The global mRNA sequencing data showed that G0S2 disruption in chickens would activate the adipose tissue‐specific peroxisomal oxidation pathway, and enoyl‐coenzyme A (CoA), hydratase/3‐hydroxyacyl CoA dehydrogenase might be a target molecule in metabolic homeostasis in the chicken adipose tissue. Our results demonstrate that the CRISPR‐Cas9 system with chicken PGCs can facilitate the production of specific genome‐edited chickens for practical applications, as well as basic research.—Park, T. S., Park, J., Lee, J. H., Park, J.‐W., Park, B.‐C., Disruption of G0/G1 switch gene 2 (G0S2) reduced abdominal fat deposition and altered fatty acid composition in chicken. FASEB J. 33, 1188–1198 (2019). www.fasebj.org